Facial swelling and dysphonia during labour: a case of Hamman's syndrome. Issue 6 (26th June 2019) - James, Rhian Elin; Bhanu, Cini; Hapuarachi, Sharleen; Leyva Caraballo, Erick
Abstract : We present the case of a previously fit and well 30-year-old primiparous woman who developed Hamman's syndrome during the second stage of labour. This is an unusual and peculiar condition, characterised by spontaneous pneumomediastinum and subcutaneous emphysema. The rarity of the condition means it can easily be misdiagnosed. Its exact aetiology is unknown, but it is believed that extreme Valsalva manoeuvre during prolonged or difficult labours may contribute to its development. Chest X-ray is the first investigation of choice in this presentation, followed by CT scanning. Fortunately, it is usually a benign condition that can be managed conservatively and resolved quickly, with no long-term effects and low risk of recurrence in future pregnancies. We are pleased to say that this case does not differ in this respect. It is, however, important to rule other more serious pathologies that present in a similar way, for example, Boerhaave syndrome, pneumothorax or pulmonary embolism.